2018
DOI: 10.3390/cryst8020107
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Fluorescence Properties of Asymmetrical Salamo-Type Tetranuclear Zinc(II) Complex

Abstract: Abstract:A new tetranuclear zinc(II) complex with an asymmetrical Salamo-type chelating ligand, H 3 L (5-methoxy-6 -hydroxy-2,2 -[ethylenedioxybis(nitrilomethylidyne)]diphenol), was synthesized and characterized using FT-IR, elemental analyses, X-ray single crystal diffraction method, UV-Vis, and fluorescence spectra. The zinc(II) complex possesses the cell parameters a = 8.1960(7) Å, b = 9.8127(8) Å, c = 16.5428(15) Å, Z = 1, V = 1172.5(2) Å 3 , R 1 = 0.0722, and wR 2 = 0.1558, and crystallizes in the triclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 61 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…The four donor atoms (N1, N2, O1, and O4) formed a base plane, and the dihedral angle of the N1-Cu1-O1 and O4-Cu1-N2 planes was at 2.09(3)°. The axial position was occupied by the oxime oxygen atom (O6); thus, the Cu1 ion possessed a slightly twisted square pyramidal geometry with the τ value τ = 0.004 (τ < 0.5) [15,61]. The distance of Cu1-O6 (2.508 (2)) was considerably longer than the Cu-O and Cu-N bonds (Cu1-O1, 1.914(2); Cu1-O4, 1.921(2); Cu1-N1, 2.014(3) and Cu1-N2, 1.964 (3) The Cu II complex crystallized in the triclinic system, space group P-1, which clearly indicated that the structure of the resulting complex was an unexpected dinuclear Cu II complex of salamo-like ligand H 2 L 2 , not an expected Cu II complex of half-salamo-like ligand HL 1 .…”
Section: Crystal Structure Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The four donor atoms (N1, N2, O1, and O4) formed a base plane, and the dihedral angle of the N1-Cu1-O1 and O4-Cu1-N2 planes was at 2.09(3)°. The axial position was occupied by the oxime oxygen atom (O6); thus, the Cu1 ion possessed a slightly twisted square pyramidal geometry with the τ value τ = 0.004 (τ < 0.5) [15,61]. The distance of Cu1-O6 (2.508 (2)) was considerably longer than the Cu-O and Cu-N bonds (Cu1-O1, 1.914(2); Cu1-O4, 1.921(2); Cu1-N1, 2.014(3) and Cu1-N2, 1.964 (3) The Cu II complex crystallized in the triclinic system, space group P-1, which clearly indicated that the structure of the resulting complex was an unexpected dinuclear Cu II complex of salamo-like ligand H 2 L 2 , not an expected Cu II complex of half-salamo-like ligand HL 1 .…”
Section: Crystal Structure Descriptionmentioning
confidence: 99%
“…The four donor atoms (N1, N2, O1, and O4) formed a base plane, and the dihedral angle of the N1-Cu1-O1 and O4-Cu1-N2 planes was at 2.09(3) • . The axial position was occupied by the oxime oxygen atom (O6); thus, the Cu1 ion possessed a slightly twisted square pyramidal geometry with the τ value τ = 0.004 (τ < 0.5) [15,61].…”
Section: Crystal Structure Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the crystal structure of complex 3, there are a pair of intramolecular hydrogen bonds C19a-H19Ba···O4 (a = 1 − x, 1 − y, 1 − z) to stabilize the whole architecture ( Figure 11, Table 3). Meanwhile, the complex 3 interlinks into one 1D infinite chain along the b axis by a weak intermolecular C11c-H11c···O3 (c = 1 − x, 2 − y, 1 − z) hydrogen bond interaction [90][91][92][93] (Figure 12). In the crystal structure of complex 3, there are a pair of intramolecular hydrogen bonds C19a-H19Ba···O4 (a = 1 − x, 1 − y, 1 − z) to stabilize the whole architecture ( Figure 11, Table 3).…”
Section: Crystal Structure Of Mn III Complexes 1 2 Andmentioning
confidence: 99%
“…The structural motifs of these coordination compound molecules may be affected by several factors, such as the performance of the ligands, the property of the central atoms, anion effects, solvent effects, and so on [50][51][52][53][54][55][56][57][58][59]. Transition metal Salamo-type coordination compounds have aroused widespread concerns for their photophysical properties [60][61][62][63][64][65][66]. Previous studies have been carried out on the mononuclear coordination compounds [67,68].…”
Section: Introductionmentioning
confidence: 99%